1991
DOI: 10.1071/ar9910417
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive semi-quantitative biotin-streptavidin ELISA for the detection of potyviruses infecting cucurbits

Abstract: The biotin-streptavidin (BA)-ELISA system was optimized for the detection of three potyviruses infecting cucurbits, the watermelon strain of papaya ringspot virus (PRSV-W), zucchini yellow mosaic virus (ZYMV) and watermelon mosaic virus 2. BA-ELISA was four to eight times more sensitive than double antibody sandwich ELISA and detected all three viruses in the nanogram range. BA-ELSA was virus-specific but did not differentiate between different pathotypes of ZYMV. The use of egg-white avidin-enzyme conjugate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Menassa et al (1986) described the detection of ZYMV in intact leaf disks by direct or indirect ELISA tests; attempts to detect ZYMV in viruliferous aphids were not satisfactory. Dietzgen & Herrington (1991) used a semiquantitative biotinstreptavidin ELISA, with a sensitivity increased 4-8 times compared to DAS-ELISA.…”
Section: Serological Techniquesmentioning
confidence: 99%
“…Menassa et al (1986) described the detection of ZYMV in intact leaf disks by direct or indirect ELISA tests; attempts to detect ZYMV in viruliferous aphids were not satisfactory. Dietzgen & Herrington (1991) used a semiquantitative biotinstreptavidin ELISA, with a sensitivity increased 4-8 times compared to DAS-ELISA.…”
Section: Serological Techniquesmentioning
confidence: 99%
“…Other diagnostic methods reported for detection of ZYMV are immunobinding, ELISA, RT‐PCR/PCR and real‐time PCR (Somowiyarjo et al. ; Dietzgen and Herrington ; Thomson et al. ; Coutts et al.…”
Section: Discussionmentioning
confidence: 99%
“…Dietzgen and Herrington () reported that RT‐PCR is more effective and more specific than ELISA for the detection of ZYMV in diseased cucurbitaceous plants. However, our study indicates that the RT‐LAMP assay is superior to the RT‐PCR assay in detection of ZYMV in infected plant tissues because the test is faster than the conventional RT‐PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Both serological and molecular diagnostic methods are available for the detection of WMV and ZYMV in routine diagnosis, such as enzyme-linked immunosorbent analysis (ELISA) [ 17 ], conventional reverse-transcription polymerase chain reaction (RT-PCR) [ 6 , 18 , 19 , 20 ], reverse transcription loop-mediated isothermal amplification (RT-LAMP) [ 21 , 22 ], and small RNA sequencing [ 11 ]. Most of these methods were not validated for their sensitivity and specificity according to the international requirements for plant pest diagnosis.…”
Section: Introductionmentioning
confidence: 99%